Assessing the Correlation Between Disease Severity Indices and Quality of Life Measurement Tools in Pemphigus - Krain, Rebecca L.; Kushner, Carolyn J.; Tarazi, Meera; Gaffney, Rebecca G.; Yeguez, Andrea C.; Zamalin, Danielle E.; Pearson, David R.; Feng, Rui; Payne, Aimee S.; Werth, Victoria P. (Frontiers in Immunology, 2019)
Pemphigus, an autoimmune blistering disease that affects the skin and mucous membranes, adversely impacts patients’ quality of life (QOL). While there are various QOL measurement tools that can be used in this disease, few studies have assessed how a patient’s change in disease severity can affect their QOL. This study aims to identify which disease severity index correlates best with the change in QOL. Fifty pemphigus patients completed QOL surveys with disease severity scored over two visits. QOL was assessed with the Autoimmune Bullous Disease Quality of Life (ABQOL), Dermatology Life Quality Index (DLQI), Skindex-29, and Short Form Survey 36 (SF-36). Disease severity was scored with the Pemphigus Disease Activity Index (PDAI) and Autoimmune Bullous Skin Disorder Intensity Score (ABSIS). Correlations between the change in QOL scores and change in disease severity were analyzed using Spearman’s coefficient (r). The change in PDAI showed a strong correlation (r=0.60-0.79) with changes in the ABQOL, Skindex-29 symptoms (Skindex-S) and Skindex-29 functioning (Skindex-F) subscales for all patients (n=50). For patients with mucosal disease (n=24), the change in PDAI showed a strong correlation with changes in the ABQOL and Skindex-S subscale. For patients without mucosal disease, the change in PDAI showed a strong correlation with the Skindex-S. The change in ABSIS showed a strong correlation with Skindex-S for all patients and patients with no mucosal involvement, but showed no strong correlations for patients with mucosal involvement. The changes in PDAI always had a stronger correlation than the changes in ABSIS scores to changes in the ABQOL, DLQI, and Skindex-29 subscales, except where the PDAI and ABSIS scores were about the same for the Skindex-S subscale in patients with no mucosal involvement (r=0.76 and r=0.77 respectively). PDAI is superior to ABSIS in its correlation with validated QOL tools. The QOL tools that appear to be of most use in clinical trials and patient management are the Skindex-S and ABQOL.